Toward a Clean World for All : An IEG Evaluation of the World Bank Group’s Support to Pollution Management - Independent Evaluation Group (World Bank, Washington, DC, 2017)
This evaluation is the first comprehensive assessment of World Bank Group's multisectoral engagement in pollution management with 534 projects and US$34 billion commitment during FY04-17. It finds that the Bank Group has made significant progress in improving pollution management in client countries although important gaps remain. World Bank efforts to set up country-level pollution monitoring systems have been relatively rare, despite a recent surge. Pollution does not get adequately prioritized in country strategies. The Bank's Country Environmental Analyses have been instrumental in prioritizing pollution in policy dialogue. Yet, they have only been prepared for 42 countries (28 percent of client countries) and the extent in which those country strategies reflect identified pollution concerns is limited. Overall, the magnitude of the Bank Group's engagement has declined as a share of the overall portfolio even as global pollution levels have risen. It has also missed opportunities to fight indoor and outdoor air pollution, which are responsible for the highest share of deaths caused by pollution. The Bank Group's climate change mitigation portfolio provides an opportunity to address outdoor air pollution, helping to build the case to client countries justifying such interventions that yield co-benefits: pollution and greenhouse gas reduction. About one-third of IFC client companies do not meet the relevant requirements for air emissions and wastewater. IEG recommends strengthening monitoring efforts, strengthening country analytical work to ensure a more comprehensive integration to the identified pollution priorities in the SCDs and subsequent CPFs, scaling up and recalibrating the World Bank’s support in pollution management, leveraging its climate change portfolio to better combat local and regional air pollution, and strengthening IFC’s advisory support to help its investment clients better comply with pollution requirements.